Differential Dorsolateral Prefrontal Cortex Proteomic Profiles of Suicide Victims with Mood Disorders - Cabello-Arreola, Alejandra (Genes (Basel), 2020)
Suicide is a major public health concern; nevertheless, its neurobiology remains unknown. An area of interest in suicide research is the dorsolateral prefrontal cortex (DLPFC). We aimed to identify altered proteins and potential biological pathways in the DLPFC of individuals who died by suicide employing mass spectrometry-based untargeted proteomics. Postmortem DLPFC from age-matched male suicide mood disorder cases (n = 5) and non-suicide mood disorder cases (n = 5) were compared. The proteins that differed between groups at false discovery rate (FDR) adjusted p-values (Benjamini–Hochberg–Yekutieli) <0.3 and Log(2) fold change (FC) >|0.4| were considered statistically significant and were subjected to pathway analysis by Qiagen Ingenuity software. Thirty-three of the 5162 detected proteins showed significantly altered expression levels in the suicide cases and two of them after adjustment for body mass index. The top differentially expressed protein was potassium voltage-gated channel subfamily Q member 3 (KCNQ3) (Log(2)FC = −0.481, p = 2.10 × 10(−09), FDR = 5.93 × 10(−06)), which also showed a trend to downregulation in Western blot (p = 0.045, Bonferroni adjusted p = 0.090). The most notably enriched pathway was the GABA receptor signaling pathway (p < 0.001). Here, we report a reduction trend of KCNQ3 levels in the DLPFC of male suicide victims with mood disorders. Further studies with a larger sample size and equal sex representation are needed.